1997
DOI: 10.1073/pnas.94.25.13677
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity: A biomarker of cell proliferation, not malignant transformation

Abstract: Telomerase activity is readily detected in most cancer biopsies, but not in premalignant lesions or in normal tissue samples with a few exceptions that include germ cells and hemopoietic stem cells. Telomerase activity may, therefore, be a useful biomarker for diagnosis of malignancies and a target for inactivation in chemotherapy or gene therapy. These observations have led to the hypothesis that activation of telomerase may be an important step in tumorigenesis. To test this hypothesis, we studied telomerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
88
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(100 citation statements)
references
References 36 publications
10
88
1
1
Order By: Relevance
“…The demonstration of endogenous/basal hTERT by NHU cells was in agreement with previous reports [23]. hTERT activity was also confirmed by assaying telomerase activity (Table 1).…”
Section: Verification Of Para-malignant Cell Linessupporting
confidence: 91%
See 1 more Smart Citation
“…The demonstration of endogenous/basal hTERT by NHU cells was in agreement with previous reports [23]. hTERT activity was also confirmed by assaying telomerase activity (Table 1).…”
Section: Verification Of Para-malignant Cell Linessupporting
confidence: 91%
“…Proliferating NHU cells express (low level) endogenous hTERT expression, as shown in this study ( Figure 1C) and elsewhere [23], as do some somatic cell types that have the capacity to switch from a quiescent to highly-proliferative phenotype. Urothelium is renowned as a low-turnover, mitotically-quiescent epithelium that has high regenerative capacity.…”
Section: Discussionsupporting
confidence: 78%
“…Activation of this enzyme enables cells to overcome replicative senescence and divide indefinitely. 18,19 Telomerase activity is considered a marker of cell proliferation, 20 as it is present in normal tissues that are highly proliferative, such as oral mucosa, 21 the basal layer of epidermis, 22 and proliferative-phase endometrium. 23 Telomerase activity is also present in a high percentage of human tumor types.…”
Section: Human Telomerase Reverse Transcriptase (Tert)mentioning
confidence: 99%
“…23 Telomerase activity is also present in a high percentage of human tumor types. 24 In malignancies, telomerase activity may simply mirror the fraction of proliferating cells; 20 however, it is also hypothesized that tumor cells may independently upregulate telomerase levels. 25 Studies have revealed that there are two major subunits contributing to in vitro activity of the telomerase enzyme complex: an intrinsic RNA component (TERC) containing a template region that binds to telomeric repeats; and a catalytic subunit with reverse transcriptase activity (TERT).…”
Section: Human Telomerase Reverse Transcriptase (Tert)mentioning
confidence: 99%
“…It has been proposed that telomerase activity correlates with cell proliferation (Belair et al, 1997) and that, within telomerase-positive cells, is differentially expressed during the cell cycle (Holt et al, 1996). Furthermore, the amount of the RNA component of the telomerase holoenzyme, but not its enzymatic activity, correlates in mouse mammary tumors with the level of histone H4 mRNA, a proliferative marker (Broccoli et al, 1996).…”
mentioning
confidence: 99%